The Impact of Backboard Placement on Chest Compression Quality: A Mannequin Study - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2019)
Introduction: High-quality chest compressions (CCs) are associated with high survival rates and good neurological outcomes in cardiac arrest patients. The 2015 American Heart Association (AHA; Dallas, Texas USA) Guidelines for Resuscitation defined and recommended high-quality CCs during cardiopulmonary resuscitation (CPR). However, CPR providers struggle to achieve high-quality CCs. There is a debate about the use of backboards during CPR in literature. Some studies suggest backboards improve CC quality, whereas others suggest that backboards can cause delays. This is the first study to evaluate all three components of high-quality CCs: compression depth, recoil depth, and rate, at the same time with a high number of subjects. This study evaluated the impact of backboards on CC quality during CPR. The primary outcome was the difference in successful CC rates between two groups. Methods: This was a randomized, controlled, single-blinded study using a high-fidelity mannequin. The successful CC rates, means CC depths, recoil depths, and rates achieved by 6th-grade undergraduate medical students during two minutes of CPR were compared between two randomized groups: an experimental group (backboard present) and a control group (no backboard). Results: Fifty-one of all 101 subjects (50.5%) were female, and the mean age was 23.9 (SD = 1.01) years. The number and the proportion of successful CCs were significantly higher in the experimental group (34; 66.7%) when compared to the control group (19; 38.0%; P = .0041). The difference in mean values of CC depth, recoil depth, and CC rate was significantly higher in the experiment group. Conclusion: The results suggest that using a backboard during CPR improves the quality of CCs in accordance with the 2015 AHA Guidelines.
Keywords: backboard; chest compression; chest compression depth; chest compression rate; mannequin; CARDIOPULMONARY-RESUSCITATION; CARDIAC-ARREST; DEPTH; CPR; MATTRESS; BED; DEFLECTION; MECHANICS; FEEDBACK; SURFACES